Pengaruh Tingkat Inflasi, Right Issue, dan Earnings Per Share (EPS) terhadap Harga Saham pada Perusahaan Industri Makanan dan Minuman yang Terdaftar di BEI Periode 2017-2021 - Andayani, Putu Risma; Werastuti, Desak Nyoman Sri (Universitas Pendidikan Ganesha, 2023)
This research uses food and beverage industry companies that have been listed on the IDX in the 2017-2021 period. Where this study uses 3 independent variables, namely there are 3 of them the inflation rate variable, the Right Issue variable, and the Earnings Per Share variable. As for the dependent variable, namely stock prices. The purpose of this study is to determine the effect of the Inflation Rate, Right Issue, and Earnings PerShare on stock prices. What was done to achieve the research objectives was to use data derived from 165 samples of financial reports or annual reports that had been determined previously through a purposive sampling technique. And processed with SPSS 25.0. The results showed that the negative inflation rate had no significant effect on stock prices, while the Right Issue had a positive and significant effect on the stock prices of food and beverage industry companies.